St. John and the Victorians - Wheeler, Michael, 1947- (Cambridge ; New York : Cambridge University Press, 2012)
"The Gospel according to St John, often regarded as the most important of the gospels in the account it gives of Jesus' life and divinity, received close attention from nineteenth-century biblical scholars and prompted a significant response in the arts. This original interdisciplinary study of the cultural afterlife of John in Victorian Britain places literature, the visual arts and music in their religious context. Discussion of the Evangelist, the Gospel and its famous prologue is followed by an examination of particular episodes that are unique to John. Michael Wheeler's research reveals the depth of biblical influence on British culture and on individuals such as Ruskin, Holman Hunt and Tennyson. He makes a significant contribution to the understanding of culture, religion and scholarship in the period"--
Machine generated contents note: Part I. The Evangelist, The Gospel, The Word: 1. The apostle of love: St John the Evangelist; 2. 'The most marvellous enigma': the fourth gospel; 3. The light of the word: incarnation; Part II. Interpretations and Representations: 4. Water into wine: the marriage at Cana; 5. Living water: the woman at the well; 6. Raising the dead: Lazarus of Bethany; 7. 'Behold thy mother': at the foot of the cross; 8. Touching the risen body: Mary Magdalene and Thomas; Afterword; Bibliography; Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Influence; Great Britain -- Civilization -- 19th century; Great Britain -- History -- 19th century; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books